Persistence of SARS-CoV-2: a new paradigm of COVID-19 management - Alhusseini, L. B.; Yassen, L. T.; Kouhsari, E.; Al Marjani, M. F. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Full attention must be given to the follow-up of patients recovered from Coronavirus disease 2019, which developed in Wuhan, China in December 2019. Among the most serious issues since the emergence of the Severe Acute Respiratory Syndrome Coronavirus 2 has been whether those who had it can experience a second episode of infection and what that implies for immunity. The earlier studies on COVID-19 disease focused primarily on the epidemiological, clinical, and radiological characteristics of patients with COVID-19. However, conclusions of these studies still require to be warranted by more careful design, larger sample size and statistically well structured studies. COVID-19 is an under-studied infection, and several aspects of viral transmission and clinical progress remain at present unclear. There is a concern about the persistence of SARS-CoV-2 on various surfaces and in the respiratory system of patients who have survived. One of the most concerning issues since the emergence of the SARS-CoV-2 is persistence in patients and whether patients can be re-infected. After hospital discharge, recovered patients were reported to have positive SARS-CoV-2 test in China, Japan, and South Korea. In addition to the persistence of the virus, SARS-CoV-2 re-infection may occur in survivors. In this paper, we focused on the evidence of persistence and re-infection of SARS-CoV-2.